Detection of Mutations in SARS-CoV-2 Genomic Clades using COVIDSeq-NGS among International Travelers. (9th November 2022) - Arshad, N; Ammad, M; Razzak, A; Ullah, R; Ul Ain, Q; Yousaf, M; Sajjad Naqvi, S; Ur Rehman, M; Noorul Hasan, T; Hussain, A; Al Yafei, Z
Abstract: Introduction/Objective: Numerous SARS-CoV-2 variants/lineages have been identified based on genome sequencing. As of June 15, 2022 almost 11, 399, 573 whole genome sequences have been deposited in the GISAID-database. Severity and spread of COVID19 is based on their efficiency of infection and to multiply in host. That largely depend upon the structural mutation in spike, ORF and N proteins etc. That happens due to translation of genomic mutations during polypeptide synthesis. Also, the mutations are region/country specific. Specific mutation and combination of mutation causes the emergence of new strains. However, the strains can migrate from one region to other through travelers. The main objective of the current study is profiling of mutations in the genome of SARSCoV2 using Next- Generation-Sequencing (NGS) in international travelers and phylogenetic analysis of the sequences to find out different clades of SARSCoV2. Methods/Case Report: A total of 557 SARSCoV2 genomes were sequenced on S4-sequencing flow-cell on NovaSeq 6000. For NGS of SARS-CoV-2 genome, Illumina, COVIDSeq kits and the protocols will be used strictly as recommended by the manufacturer. After NGS the analysis was done followed by FASTA sequences retrieval, mutations recording and phylogeny. Results (if a Case Study enter NA): This study reports 11 clades (19A, B, 20A, B, C, D, 20E; EU1, 20G, 20H; Beta V2, 20I: Alpha V1, 21D; and Eta) for the first time in international travelers. To best of our knowledge, this is the first report of the COVIDSeq approach for detection of mutation in SARSCoV2 genomic clades. The study revealed some dominants mutations was (Orf1a: P2018Q, K1053R, E176V, Orf1b: A520V, T2165A, S: D1127G, D614G, L18F etc. in other genes). Conclusion: Profiling of common mutations among travelers could fill some gaps about the existence of SARS-CoV-2 variants information. However, further studies are needed to consolidate these findings before to be utilized for development of a potential therapeutic strategy.